Perceptions of disaster resilience in four Texas coastal communities. Issue 3 (4th May 2019) - Goidel, Kirby; Horney, Jennifer A.; Kellstedt, Paul M.; Sullivan, Emily; Brown, Stephanie E. V.
ABSTRACT: Scholars and practitioners have long noted the importance of community resilience to disaster recovery and environmental risk mitigation. Yet we know surprisingly little about how local residents perceive the resilience of their local communities, including how closely their perceptions align with objective measures of resilience or whether these perceptions affect community engagement and support for resilience building activities and policies. In this paper, we utilise the results of public opinion surveys of residents of four Texas coastal shoreline counties (Brazoria, Nueces, Galveston, and Cameron) to address this gap in the literature. The results reveal that perceptions of community preparedness largely reflect social trust and disaster awareness while perceptions of recovery reflect perceived risks and preparedness.